2018
DOI: 10.1371/journal.pcbi.1006376
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and prediction of clinical symptom trajectories in Alzheimer’s disease using longitudinal data

Abstract: Computational models predicting symptomatic progression at the individual level can be highly beneficial for early intervention and treatment planning for Alzheimer’s disease (AD). Individual prognosis is complicated by many factors including the definition of the prediction objective itself. In this work, we present a computational framework comprising machine-learning techniques for 1) modeling symptom trajectories and 2) prediction of symptom trajectories using multimodal and longitudinal data. We perform p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 42 publications
8
105
0
1
Order By: Relevance
“…Previous studies evaluating biomarker combinations 9,12 or machine learning demonstrated that biomarker combinations can enhance the accuracy of predicting cognitive decline or conversion to dementia 20,21 . Consistently, we found increasing prediction accuracy as model estimation was informed by more biomarker modalities.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies evaluating biomarker combinations 9,12 or machine learning demonstrated that biomarker combinations can enhance the accuracy of predicting cognitive decline or conversion to dementia 20,21 . Consistently, we found increasing prediction accuracy as model estimation was informed by more biomarker modalities.…”
Section: Discussionsupporting
confidence: 86%
“…Machine learning, which is instrumental for data mining, 17 is well suited to identify biomarker sets for predicting cognitive decline. Here, recent machine-learning approaches to AD biomarker data showed that sets of imaging and CSF-derived markers discriminated MCI and AD patients from healthy controls 18 and predicted the rate of future cognitive decline 19,20 and time to symptom onset. 21 A limitation of machine learning is, however, that algorithms may perform well in the sample they were trained on but rarely generalize to new data.…”
Section: Introductionmentioning
confidence: 99%
“…When predicting future cognitive change, however, brain imaging might aid a prognosis with greater clinical utility that cannot be easily obtained otherwise. Most previous studies that predicted future change restricted their analysis to whether patients with mild cognitive impairment (MCI) converted to Alzheimer’s disease (AD) (Davatzikos et al, 2011; e.g., Eskildsen et al, 2015; Gaser et al, 2013; Korolev et al, 2016) or predicted membership in data-driven trajectory-groups of future decline (Bhagwat et al, 2018). Predicting future cognitive decline on a continuum (instead of forming distinct diagnostic labels from cognitive data) better characterizes the underlying change in abilities on an individual level.…”
Section: Introductionmentioning
confidence: 99%
“…al. [2], subjects from the ADNI1 cohort were used for trajectory modelling, dividing the dataset between "Stable" and "Decline" subjects, based on the Mini Mental State Evaluation clinical scores. We selected a subset of these subjects in our dataset: 134 "Stable" subjects, and 113 "Decline" subjects.…”
Section: Training Protocolmentioning
confidence: 99%
“…al. [2] who have proposed a siamese network to predict the evolution of patients by using measures computed from MRI images and a cognitive score. On one hand, as we would like to take into account 3D MRI, our network is made of several layers of convolutional layers for each of its branches.…”
Section: Introductionmentioning
confidence: 99%